Separating item-related electrophysiological indices of retrieval effort and retrieval orientation - Dzulkifli, Mariam Adawiah; Sharpe, Helen L.; Wilding, Edward (Elsevier Inc., 2004)
The relationship between two classes of retrieval process—retrieval orientation and retrieval effort—was investigated using electrophysiological (ERP) and behavioural measures. ERPs were recorded during retrieval phases of exclusion tasks in which participants focused on retrieval of either phonological or semantic associates that were generated in a prior study phase. Participants were separated into two groups on the basis of the relative accuracy of their memory judgments in the retrieval tasks (high vs. low relative difficulty) as a means of assessing retrieval effort. The critical contrasts were between the ERPs evoked by unstudied test items separated according to group and emphasis of the retrieval task (semantic vs. phonological). Reliable differences according to task were evident in the high relative difficulty group only. This finding is consistent with the view that, for this task pair at least, ERPs are sensitive to the processes set in train in pursuit of task relevant information (retrieval orientations) only when relative difficulty is high.